2021
DOI: 10.1039/d1gc02102h
|View full text |Cite
|
Sign up to set email alerts
|

Mild selective oxidative cleavage of lignin C–C bonds over a copper catalyst in water

Abstract: The conversion of lignin into aromatics as commodity chemicals and high-quality fuels is a highly desirable goal for biorefineries. However, the presence of robust inter-unit carbon-carbon (C–C) bonds in natural...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 66 publications
1
30
0
Order By: Relevance
“…S4†). More importantly, compared to various literature reports (Table S2†), 11–13,18,20,34,35,39,48–55 our present catalytic system using the HPMoV-BMIM-SO 3 H IL catalyst exhibited obvious advantages of mild catalytic conditions, high efficiency, and easy catalyst recovery towards the selective cleavage of lignin β-O-4 models (PP-ol and PP-one).…”
Section: Resultsmentioning
confidence: 69%
“…S4†). More importantly, compared to various literature reports (Table S2†), 11–13,18,20,34,35,39,48–55 our present catalytic system using the HPMoV-BMIM-SO 3 H IL catalyst exhibited obvious advantages of mild catalytic conditions, high efficiency, and easy catalyst recovery towards the selective cleavage of lignin β-O-4 models (PP-ol and PP-one).…”
Section: Resultsmentioning
confidence: 69%
“…The selective cleavage of β-O-4, β-1, and C-C bonds catalyzed by copper and alkali solutions to produce high yields of aromatic acids and phenol was first reported by Hu and co-workers. The DFT calculations showed that the oxidation of β-O-4 ketone to peroxide intermediates by Cu and O2 reduced the dissociation energy of the Cα-Cβ bond (Hu et al 2021b). The mechanism of HDO reaction was investigated during the decomposition of anisole over a bifunctional catalyst consisting of metal and Brønsted acid using DFT.…”
Section: Table 2 Computational Study On Catalytic Degradation Of Lign...mentioning
confidence: 99%
“…13 However, extremely challenging reaction parameters, involving high temperatures and hydrogen gas, were necessary to produce the dissociation of C−C bonds. Even Wang et al described the outstanding yields of aromatic acids and phenols in water at 30 °C after the selective breaking of C−C bonds in β-1 and β-O-4 linkages catalyzed by inexpensive copper and a base, 14 while homogenous catalyst recycling and product separation might be challenging. Thus, developing a sustainable methodology for lignin C−C bond breakage under mild circumstances, such as the most common β-O-4 models, is desirable.…”
Section: Introductionmentioning
confidence: 99%